2017
DOI: 10.7600/jspfsm.66.407
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a self-reported physical activity questionnaire assessment for Japanese children

Abstract: The study aimed to assess a self-reported questionnaire about physical activity (PA) from the Health Behaviour in School-aged Children (HBSC) using triaxial accelerometer as a criterion. Elementary school boys (N=292) and girls (N=313) in the fourth grade and higher completed the questionnaire and wore an accelerometer for at least 10 h/day for at least 4 days. The phi coefficients of the chi-square test 2-way tables (active/inactive as measured using the HBSC questionnaire × achievement/non-achievement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Therefore, the actual amount of physical activity might have been underestimated. Although the Health Behavior in School-aged Children Study (HBSC) questionnaire, which was used as a reference in the development of the questionnaire for this study, was confirmed to be valid and reliable [19,34,35], it overestimated moderate-to-vigorous physical activity compared with an accelerometer and reported sexual differences in the accuracy of responses [35]. These factors may have influenced the result in the subanalysis.…”
Section: Association Between Physical Activity and Depressive Symptomsmentioning
confidence: 76%
“…Therefore, the actual amount of physical activity might have been underestimated. Although the Health Behavior in School-aged Children Study (HBSC) questionnaire, which was used as a reference in the development of the questionnaire for this study, was confirmed to be valid and reliable [19,34,35], it overestimated moderate-to-vigorous physical activity compared with an accelerometer and reported sexual differences in the accuracy of responses [35]. These factors may have influenced the result in the subanalysis.…”
Section: Association Between Physical Activity and Depressive Symptomsmentioning
confidence: 76%
“…The equation for locomotive activity can evaluate both ambulation and running, while the equation for nonlocomotive activity is good at estimating irregular motions associated with daily activities, such as sweeping, clearing away, and throwing a ball. This algorithm has previously been used in investi-*Correspondence: hikihara.yuki@it-chiba.ac.jp gative studies such as the validation of MVPA with questionnaire 8) , the contribution of types of physical education to MVPA 9) , and comparisons of MVPA during the school year and summer vacation 10) .…”
Section: Introductionmentioning
confidence: 99%